Performance evaluation of drip irrigation and fertigation system for sweet maize and telfairia occidentalis (2007)
Studies were conducted to evaluate the performance of drip irrigation and fertigation system on the yields of sweet maize and telfairia occidentalis. Three treatments: watering once per week (6.38 litres) (WI), twice (11.66 litres) (W2) and thrice (17.16 litrcs) (W3) were applied to sweet maize. Four treatments: 12 litres (WI), 15 litres (W2) 17.0 litres (W3), 22.05 litres (W4) and four fertigation levels: 54.6kg/ha (F1); 68.06kg/ha (F2); 81.92kg/ha (F3) and 95.39kg/ha (F4) were applied to telfairia occidentalis. Growth and yield of the crops were monitored. W2 was optimum for sweet maize cultivation while (F2W2) was recommended for telfairia occidentalis.